2011
DOI: 10.1007/s11606-011-1894-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Participant Feedback to Continuing Medical Education Presenters in Internal Medicine: A Mixed-Methods Study

Abstract: BACKGROUND: Feedback is essential for improving the skills of continuing medical education (CME) presenters. However, there has been little research on improving the quality of feedback to CME presenters. OBJECTIVES: To validate an instrument for generating balanced and behavior-specific feedback from a national cross-section of participants to presenters at a large internal medicine CME course. DESIGN, SETTING, AND PARTICIPANTS: A prospective, randomized validation study with qualitative data analysis that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…However, age per se did not seem to effect feedback-seeking behaviour (Lee et al 2009). Although, Wittich et al (2012) found that registrars perceived older consultants to be better at providing feedback than their younger colleagues, perhaps because they equated experience with excellence. However, Kogan et al (2012) report that faculty approaches to feedback are based rather on more contextual factors such as their own views on how effective they were at delivering feedback and relational issues, rather than age or experience alone.…”
mentioning
confidence: 96%
“…However, age per se did not seem to effect feedback-seeking behaviour (Lee et al 2009). Although, Wittich et al (2012) found that registrars perceived older consultants to be better at providing feedback than their younger colleagues, perhaps because they equated experience with excellence. However, Kogan et al (2012) report that faculty approaches to feedback are based rather on more contextual factors such as their own views on how effective they were at delivering feedback and relational issues, rather than age or experience alone.…”
mentioning
confidence: 96%
“…The Wood et al and Wittich et al tools measure similar concepts to the CORD‐EM tool, but the CORD‐EM tool has validity evidence specifically for summative evaluation use by conference planners. Our study is also the first to evaluate a speaker evaluation tool at—and explicitly for—a national medical conference.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are several resources that describe how to give effective presentations . However, there are few resources with supportive evidence for medical conference planners to evaluate their speakers . The CME literature in recent years has emphasized the need for tangible learning outcomes, but the impractical nature of designing, examining validity evidence, and administering pre‐ and posttests to all CME participants for all lectures leaves conference planners with only speaker evaluation forms to help make practical decisions about speakers for the following year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also wished to know in residents' own words what they learned from the co-management experience. By asking a combination of closed-and open-ended survey questions [15], we sought to assess the association between types of co-management interactions and the following outcomes: (1) whether residents received feedback on patient management, (2) residents' perceptions of patient benefit from co-managing, and (3) common learning themes. To examine these questions, we surveyed residents from FM and IM residencies with existing IBHC involvement in their primary care continuity clinics.…”
Section: Introductionmentioning
confidence: 99%